1996
DOI: 10.1103/physrevlett.76.708
|View full text |Cite
|
Sign up to set email alerts
|

Multistability and Delayed Recurrent Loops

Abstract: Multistable dynamical systems have important applications as pattern recognition and memory storage devices. Conditions under which time-delayed recurrent loops of spiking neurons exhibit multistability are presented. Our results are illustrated on both a simple integrate-and-fire neuron and a Hodgkin-Huxley-type neuron, whose recurrent inputs are delayed versions of their output spike trains. Two kinds of multistability with respect to initial spiking functions are found, depending on whether the neuron is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
170
0
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(180 citation statements)
references
References 27 publications
(16 reference statements)
4
170
0
4
Order By: Relevance
“…Moreover, the presence of delays often results in patterns of oscillatory behaviour that repeat from time to time and that strongly depend on the initial conditions, multi-stability being a wellknown feature in delayed systems [6,7]. In addition, time delays add new degrees of freedom, which can result in the delayed system having a high-dimensional dynamics similar to that of spatio-temporal systems [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of delays often results in patterns of oscillatory behaviour that repeat from time to time and that strongly depend on the initial conditions, multi-stability being a wellknown feature in delayed systems [6,7]. In addition, time delays add new degrees of freedom, which can result in the delayed system having a high-dimensional dynamics similar to that of spatio-temporal systems [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Multistability in a delayed neural network has been extensively studied in the literature, in particular for delayed neural recurrent loops [8,9], and experimentally in electrical circuits [9] and in recurrently clamped neurons [10]. Foss et al [8] studied neural recurrent inhibitory loops using the well-known HodgkinHuxley model and found three coexisting attracting periodic solutions by computer simulation. Ma and Wu [17,18] showed that the phenomenological spiking neuron model incorporating the firing process and the absolute refractory period can generate a large number of asymptotically stable periodic solutions with predictable patterns of oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence of multiple stable patterns in neural networks is the basis of the mechanism for (associative) content-addressable memory storage and retrieval [8,13,14,20,22] where each stable equilibrium is identified with a static memory, while stable periodic orbits are associated with temporally patterned spike trains [4,8,9]. Periodic patterns exhibited in neural networks have been linked to a variety of rhythms, which are associated with important behavioral and cognitive states in the nervous system, including attention, working memory, associative memory, object recognition, sensory motor integration and perception processing [5,7,15].…”
Section: Introductionmentioning
confidence: 99%
“…At the single neuron level and in ensembles of coupled neurons, delays have been shown to generate instabilities, multi-stability, chaotic oscillations and oscillation death (Foss et al 1996;Pakdaman et al 1996;Vibert et al 1998;Foss & Milton 2000;Sainz-Trapaga et al 2004;Masoller et al 2008). When the neurons are coupled through both the instantaneous and the delayed collective mean field, by varying the delay one can control (i.e.…”
Section: Introductionmentioning
confidence: 99%